2019
DOI: 10.14198/jhse.2020.153.06
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality in sports coaching, skill acquisition and application to surfing: A review

Abstract: The last decade, notably the past two years, have seen significant advancements in virtual reality (VR) technology, especially within the development of 3D and 360° virtual environments. Smart Phone technology now allows for head mounted display of this environment which is much more user friendly and cost effective. Sport training can now take full advantage of the improved quality of operating systems and as a result, VR provides visual simulations and immersive, interactive environments. VR technology is be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 60 publications
0
39
0
Order By: Relevance
“…Given these advancements, a wide range of industries are racing to embrace the new technology for training purposes before fully considering all implications. Integrations across the sporting domain are numerous and widespread (Düking et al, 2018 ), and recent work has examined its applicability to training skills such as soccer goalkeeping (Stinson and Bowman, 2014 ), rowing (Ruffaldi and Filippeschi, 2013 ), surfing (Farley et al, 2020 ), and marksmanship (Rao et al, 2018 ), to name a few. The expanding use of VR technology for acquisition or enhancement of sport skills has great promise, as a virtual world makes it possible to create training environments in which learning can take place that would otherwise be too costly, risky, or difficult to produce (Champney et al, 2014 ; Carruth, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given these advancements, a wide range of industries are racing to embrace the new technology for training purposes before fully considering all implications. Integrations across the sporting domain are numerous and widespread (Düking et al, 2018 ), and recent work has examined its applicability to training skills such as soccer goalkeeping (Stinson and Bowman, 2014 ), rowing (Ruffaldi and Filippeschi, 2013 ), surfing (Farley et al, 2020 ), and marksmanship (Rao et al, 2018 ), to name a few. The expanding use of VR technology for acquisition or enhancement of sport skills has great promise, as a virtual world makes it possible to create training environments in which learning can take place that would otherwise be too costly, risky, or difficult to produce (Champney et al, 2014 ; Carruth, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further virtual applications were also found in training science and could also be used in performance coaching. The increased training effect led significantly to skill improvement [28]. Previous studies indicated that artificial stress initiated via VR is comparable to stress induction "in vivo".…”
Section: Virtual Reality and High-risk Sportmentioning
confidence: 88%
“…Virtual reality and immersive technology advances have enabled athletes to train in simulated environments when they cannot train in their real-life environments due to, for example, adverse weather conditions, injury or the very nature of the sport ( Farley et al, 2020 ). Training of medical, military and aviation personnel using this technology has also been beneficial in recent decades ( Langfield, 2019 ).…”
Section: Virtual Reality Technology Usementioning
confidence: 99%
“…Training of medical, military and aviation personnel using this technology has also been beneficial in recent decades ( Langfield, 2019 ). The use of virtual reality and immersive video technology to enable athletes to specifically practise their reaction time skills, their decision making skills as well as their concentration skills when they are not able to compete, such as when rehabilitating from injury, for example, has been a positive application of this technology for a number of years ( Panchuk et al, 2018 ; Farley et al, 2020 ). VR technology has also been used effectively to treat clinical conditions including anxiety, paranoia and phobias across various populations ( Coyle et al, 2011 ; Gega et al, 2013 ; Flood, 2016 ; Kirwan, 2016b ).…”
Section: Virtual Reality Technology Usementioning
confidence: 99%